Plasma IGF1 and 17β-Estradiol Concentrations During the Follicular Wave in Llamas - Gallelli, María F.; Bianchi, Carolina; Zampini, Enzo; Aba, Marcelo; Gambarotta, M.; Miragaya, Marcelo (Frontiers in Veterinary Science, 2020)
The aim of this study was to characterize the temporal association between follicular waves and circulating concentrations of 17β-estradiol (E2) and IGF1 in llamas. Follicular waves could be clearly divided in three phases: growth, plateau and regression; with a mean duration of 18.8 ± 0.32 days. All follicular waves showed overlapping, so that as one dominant follicle was regressing, another one was growing. E2 plasma concentration showed a wavelike pattern, similar to that followed by the dominant follicle; reaching its maximum concentration at the end of the growth phase and decreasing at the end of the plateau phase. IGF1 also showed variations during the follicular wave. It tended to increase during the growth phase and decreased toward Days 14 and 16. IGF1 reached its maximum concentration before E2 did (5 ± 0.8 vs. 7.2 ± 0.5 days after wave emergence) and before the maximum follicular diameter was attained (10.2 ± 0.46 days after wave emergence). Both hormones started to rise again in coincidence with the development of a new follicular wave. The observed profiles allow to suggest that IGF1 could have a role on folliculogenesis and ovarian steroideogenesis in llamas, as reported for other species.